Acute effects of spinal bracing on scapular kinematics in adolescent idiopathic scoliosis. (August 2017) - Gur, Gozde; Turgut, Elif; Ayhan, Cigdem; Baltaci, Gul; Yakut, Yavuz
Abstract: Background: Bracing is the most common nonsurgical treatment for adolescent idiopathic scoliosis. Spinal braces affect glenohumeral and scapulothoracic motion because they restrict trunk movements. However, the potential spinal-bracing effects on scapular kinematics are unknown. The present study aimed to investigate the acute effects of spinal bracing on scapular kinematics in adolescent idiopathic scoliosis. Methods: Scapular kinematics, including scapular internal/external rotation, posterior/anterior tilting, and downward/upward rotation during scapular plane elevation, were evaluated in 27 in-brace and out-of-brace adolescent idiopathic scoliosis patients with a three-dimensional electromagnetic tracking system. Data on the position and orientation of the scapula at 30°, 60°, 90°, and 120° humerothoracic elevation were used for statistical comparisons. The paired t -test was used to assess the differences between the mean values of in-brace and out-of-brace conditions. Findings: The in-brace condition showed significantly increased ( P  < 0.05) scapular anterior tilting and decreased internal rotation in the resting position on the convex and concave sides; increased scapular downward rotation at 120° humerothoracic elevation on the convex side and at 30°, 60°, 90°, and 120° humerothoracic elevation on the concave side; increased scapular anterior tilt at 30°, 60°, 90°, and 120° humerothoracic elevation on the convex and concave sides; and decreased ( P  < 0.05) maximal humerothoracic elevation of the arm. Interpretation: Spinal bracing affects scapular kinematics. Observed changes in scapular kinematics with brace may also affect upper extremity function for adolescents with idiopathic scoliosis. Therefore, clinicians should include assessments of the glenohumeral and scapulothoracic joints when designing rehabilitation protocols for patients with adolescent idiopathic scoliosis. Highlights: Spinal bracing altered scapular kinematics in adolescent idiopathic scoliosis patients. Spinal bracing increased scapular anterior tilting and decreased internal rotation in rest. Spinal bracing increased scapular downward rotation and anterior tilting during arm elevation. Spinal bracing decreased the maximum humerothoracic elevation level.